Staying Physically Active During the Quarantine and Self-Isolation Period for Controlling and Mitigating the COVID-19 Pandemic: A Systematic Overview of the Literature - Chtourou, Hamdi; Trabelsi, Khaled; H'mida, Cyrine; Boukhris, Omar; Glenn, Jordan M.; Brach, Michael; Bentlage, Ellen; Bott, Nick; Shephard, Roy Jesse; Ammar, Achraf; Bragazzi, Nicola Luigi (Frontiers in Psychology, 2020)
The COVID-19 pandemic represents an unprecedented public health concern worldwide. Characterised by a rapid and high frequency of human-to-human transmission, the World Health Organisation has recommended the implementation of public health measures, such as isolation of all individuals suspected of infection with this disease for a 14-day quarantine period, while governments have introduced "social distancing" and "lock-downs" of entire populations of varying severity to curtail the spread of COVID-19. Recent studies about COVID-19 have further suggested there are significant sleep problems and psychological disorders (e.g., stress, anxiety, depression) associated with the reduction of movement and activities, plus the reduction of normal social interaction. There has been no study examining the effect of being physically active at home during such periods of isolation. However, based on studies of other diseases and pathologies, potentially useful tactics to overcome these negative effects may include home-based exercise, exergaming, dancing to music and participation in yoga.